A sociology of counter‐revolution in Egypt. Issue 9 (2nd August 2021) - Said, Atef
Abstract: In this article I interrogate three misapprehensions around the concept of counter‐revolution: (1) defining the old regime, (2) defining counter‐revolution's temporal boundary, and (3) different meanings of the countering actions. Using Egypt as a case study, I develop and apply a disaggregated and temporally sensitive framework to analyze the counter‐revolution. I argue that counter‐revolution was instigated during the revolutionary crisis (25 January–11 February 2011), accrued momentum during the extended transitional period (12 February 2011–30 June 2013) and achieved a decisive victory after the military coup of 3 July 2013. I interrogate the varieties of counter‐revolutionary actions in these periods: repression and propaganda, adopting a project of containment during the transitional period, then launching unlimited repression campaigns against revolutionaries, and expanding military rule. This framework helps make sense of how different forces change their positions over time, and of the contradictions and the dynamism of counter‐revolutionary actions.